Profile of perampanel and its potential in the treatment of partial onset seizures - Rheims, Sylvain (Dove Medical Press, 2013)
Perampanel (PER) is a novel antiepileptic compound that decreases neuronal excitability by modulating glutamatergic transmission through selective noncompetitive blockade of AMPA receptors. PER has been evaluated in three pivotal placebo-controlled randomized trials as adjunctive therapy in adult drug-resistant partial epilepsy. In comparison to placebo, adjunctive PER effectively reduces seizure frequency. The relative risk of the responder rate (95% confidence interval [CI]) was thus 1.60 (1.08–2.36), 1.79 (1.42–2.25) and 1.66 (1.24–2.23) for once-daily PER 4 mg/day, 8 mg/day and 12 mg/day, respectively. The most common adverse events associated with PER were nonspecific central nervous system side effects. Some concerns have been raised about risk of clinically significant weight gain and of psychiatric adverse events. Long-term open-label extensions of the three pivotal trials are underway. PER has recently been approved both in Europe and in the USA for the adjunctive treatment of partial onset seizures in patients aged 12 years and above. However, in the absence of a direct comparison between PER and other licensed antiepileptic drugs’ efficacy and tolerability, the clinical advantages of PER over the other drugs in intractable partial epilepsy remains to be determined.